The Rhythm, Routinization, and Reroutinization:A New Perspective on the Health Practices of Rural Residents and Their Generation in the Context of Rural Revitalization (The Journal of Medicine, Humanity and Media, 2025)
In this field study, it is found people in the three villages in the southwest part of Shandong Province have developed a practice of jogging and speed-walking on one side and eating edible wild herbs on the other in recent years as a way to keep healthy. Essentially this routinized daily life habit is the result of the transition of the health consciousness guiding their health practice from the traditional concept of “when old, one needs to be less physically active”, to the new concept of” when old, one still needs to keep some physical activities”. This forms their new daily life routine.The “spin-offs” of people's traditionally routinised health practices have then been re-routinised. The sense of health practice of ‘living longer but moving less’ contained in the traditional routine daily life has a strong endogenous power to produce daily health practice. We should believe in and encourage this endogenous force and maintain optimistic expectations for the self-health practices of rural older people.
Keywords: Health; Jog; Edible wild herbs; Practice; Routinization